Individual taxpayer assessment performance under self- assessment system in Malaysia - Mat Udin, Noraza; Md. Idris, Kamil; Mohd Hanefah, Mustafa (2011)
The revert from the Official Assessment System (OAS) to the Self-Assessment System (SAS) in Malaysian tax system beginning year 2004 for individual taxpayers, forces taxpayers to perform the primary function of SAS i.e. income assessment task previously carried out by trained tax officers. The primary function is related to determining the correct amount of tax liability and getting the tax return accurate. Hence, the successful implementation of SAS relies heavily on the acceptance and cooperation of taxpayers. This study serves to evaluate the income assessment performance of taxpayers and its influential factors. Using Libby’s (1995) Antecedents and Consequences of Knowledge model as the underlying framework, this study examines the effect of factors such as knowledge in taxation, complexity of tax laws, attitude towards paying tax, probability of being detected, taxpayer assistance, general problem solving ability, experience and demographic variables on taxpayer assessment performance. Due to the nature of variables in this study which intends to elicit self ability and knowledge of a particular individual, a quasi-experimental design were chosen as the data collection method. In order to get the involvement from the real taxpayers, this study employs purposive sampling frame by choosing the UUM KL masters students. The results of this study provide empirical evidence that in order to perform their responsibilities well, taxpayers must possess knowledge in taxation. The relationship of knowledge and performance has been examined in the context of experts such as auditors and tax professionals. This study reveals that this relationship also exist in the context of novice, nevertheless the role of knowledge in the expert and novice model is slightly different due to the different nature of expert and novice knowledge.